The role of the natural aquatic environment in the dissemination of extended spectrum beta-lactamase and carbapenemase encoding genes: A scoping review. (1st August 2020) - Hooban, Brigid; Joyce, Aoife; Fitzhenry, Kelly; Chique, Carlos; Morris, Dearbháile
Abstract: The natural aquatic environment is a significant contributor to the development and circulation of clinically significant antibiotic resistance genes (ARGs). The potential for the aquatic environment to act as a reservoir for ARG accumulation in areas receiving anthropogenic contamination has been thoroughly researched. However, the emergence of novel ARGs in the absence of external influences, as well as the capacity of environmental bacteria to disseminate ARGs via mobile genetic elements remain relatively unchallenged. In order to address these knowledge gaps, this scoping literature review was established focusing on the detection of two important and readily mobile ARGs, namely, extended spectrum beta-lactamase (ESBL) and carbapenemase genes. This review included 41 studies from 19 different countries. A range of different water bodies including rivers (n = 26), seawaters (n = 6) and lakes (n = 3), amongst others, were analysed in the included studies. ESBL genes were reported in 29/41 (70.7%) studies, while carbapenemase genes were reported in 13/41 (31.7%), including joint reporting in 9 studies. The occurrence of mobile genetic elements was evaluated, which included the detection of integrons (n = 22), plasmids (n = 18), insertion sequences (n = 4) and transposons (n = 3). The ability of environmental bacteria to successfully transfer resistance genes via conjugation was also examined in 11 of the included studies. The findings of this scoping review expose the presence of clinically significant ARGs in the natural aquatic environment and highlights the potential ability of environmental isolates to disseminate these genes among different bacterial species. As such, the results presented demonstrate how anthropogenic point discharges may not act as the sole contributor to the development and spread of clinically significant antibiotic resistances. A number of critical knowledge gaps in current research were also identified. Key highlights include the limited number of studies focusing on antibiotic resistance in uncontaminated aquatic environments as well as the lack of standardisation among methodologies of reviewed investigations. Graphical abstract: Image 1 Highlights: Evaluation of natural aquatic reservoirs globally for antibiotic resistance. Particular focus upon water bodies free from nearby point contaminant discharges. 80.5% of studies detected one or more ESBL and/or carbapenemase gene. 90.2% of studies identified at least one type of mobile genetic element. Results highlight water bodies are natural reservoirs for antibiotic resistance.